2003
DOI: 10.1088/0953-8984/15/6/306
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction investigation of the crystal and magnetic structure of the new ThCo4B compound

Abstract: The crystal and magnetic structures of a new ternary phase in the Th-Co-B system have been investigated by high resolution neutron diffraction. The spontaneous magnetization and Curie temperature were determined by magnetic measurements. The ThCo 4 B phase crystallizes in a hexagonal crystal structure, space group P6/mmm with a = 5.088 Å and c = 7.003 Å. ThCo 4 B orders ferromagnetically at 303 K, a temperature much smaller than that of the isotypic RCo 4 B where R is a rare-earth element or yttrium. The Co ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…The Co atoms provide above 80 and 90% contributions to the total DOS at the Fermi level for spin up and down, respectively. ThCo 4 B, contrary to isostructural UCo 4 B compound [5], is magnetically ordered below 303 K [4], and the saturation magnetization obtained from the 4 K isothermal magnetization curve is equal to 1.5±0.1 µ B /f.u. Neutron diffraction measurements gave magnetic moments aligned along the c-axis of the hexagonal structure in the whole ordered temperature region [4].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The Co atoms provide above 80 and 90% contributions to the total DOS at the Fermi level for spin up and down, respectively. ThCo 4 B, contrary to isostructural UCo 4 B compound [5], is magnetically ordered below 303 K [4], and the saturation magnetization obtained from the 4 K isothermal magnetization curve is equal to 1.5±0.1 µ B /f.u. Neutron diffraction measurements gave magnetic moments aligned along the c-axis of the hexagonal structure in the whole ordered temperature region [4].…”
Section: Resultsmentioning
confidence: 91%
“…The calculations were carried out for the hexagonal structure with 12 atoms per unit cell (two formula units) and experimental values of the lattice constants [4]. We assumed the following electron configurations of atoms: core + semi core electrons (5d6s) + valence electrons (6p7s7p6d5f ) for Th atoms, core + semi core electrons (3s3p) + valence electrons (4s4p3d) for Co atoms, and finally on B atom 1s electrons were treated as semi core, and (2s2p3d) electrons as valence ones.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RCo 4 B structure has two R sites (1a and 1b), two others for Co atoms (2c and 6i) and one for boron (2d). It has been shown that the Co 2c site, in ThCo 4 B is the only site, which exhibits a significant magnetic moment [12], whereas both of the Th and Co 6i sites carry a negligible magnetic moment. On the contrary, in YCo 4 B both Co 2c and Co 6i sites do carry a magnetic moment.…”
Section: Introductionmentioning
confidence: 99%